PENGARUH KEMISKINAN DAN UPAH MINIMUM PROVINSI TERHADAP KETIMPANGAN PENDAPATAN DI PULAU SUMATERA INDONESIA - Munzi Riandi; Cut Risya Varlitya (JURNAL EKOMBIS, 2020)
This study aims to determine the effect of poverty and province minimum wages on income inequality on the island of Sumatra, Indonesia. The income inequality used is the Gini coefficient. The research data use panel data with ten provinces and four years from 2014-2017. The model used is the Fixed Effect Model (FEM). The results show that wages have a negative and significant effect on inequality. The other hand, poverty has a positive and significant effect on income inequality. The impact of poverty is higher than the wages of 0.20. This study recommends that the government should encourage policies to increase wages and reduce poverty. One of them is by way of better income retribution and improvement of education programs for the poor so that there will be opportunities for work and equity.Keywords: Income Inequality, Gini Coefficient, Province Minimum Wage, Poverty.